How compliant are beverage employees to occupational health and safety regulations? - L. Chetty; J. Jelsma; S. Maart (AOSIS, 2009)
This observational study was undertaken to identify thehealth and safety violations of employees at a specific beverage manufac-turing company.  A  site inspection and observation of all employees employedat this specific beverage company was conducted by the researcher over 2 days. Employees were observed for 12 hours per day with the morningshift on Day 1 and the afternoon shift on Day 2. A  sample of conveniencewas used in that every employee who was present on those days was included. Descriptive statistics were used to analyze the data set. There were a total of 212 employees and 332 behaviours observed during thisstudy period. Unsafe handling and behaviour was observed in 55% of observations. Incorrect manual lifting techniques was the most frequent health and safety violation observed. In the 48 manual lifting behaviours observed, correct practice was observed in only three cases.  It is clear thatmore healthcare education and practical training is required in the area of manual lifting techniques. It is clear that more practical training is required in the area of manual handling.